Aktivitas Antioksidan dan Organoleptik Brownies Crispy dengan Penambahan Bubuk Cascara Arabika Kintamani (Coffea arabika L.) - Jason Patrick Kenardi; Sayi Hatiningsih; I Putu Agus Artawan; Ida Ayu Agung Prapita Hermayuli; Ni Made Mutia Pradnyawangi; Alizza Zahira Prameswari (Jurnal Teknologi dan Mutu Pangan, 2026)
Cascara has the potential to provide bioactive compounds, making it suitable as an ingredient in crispy brownies. This study aims to evaluate the effect of cascara powder concentration on the chemical and sensory properties of crispy brownies. This study employed a completely randomized design with varying concentrations of cascara powder (0%, 2.5%, 5%, 7.5%, 10%) and three replicates. The data were analyzed using ANOVA, followed by a DMRT post hoc test at a 95% confidence level. The results showed that the addition of cascara powder significantly increased antioxidant activity (61.24–78.91%) and total phenolic content (29.67–97.44 mg GAE/g). The addition of cascara powder also had a significant effect on hedonic aspects, including assessments of color, aroma, taste, and overall acceptability, as well as texture and taste scoring tests. It can be concluded that the optimal formulation is the addition of 10% cascara powder, which yields antioxidant activity of 78.91% and total phenolic content of 97.44 mg GAE/g, with product characteristics including a dark brown color, a slightly coarse texture, and a slightly bitter taste. This study can contribute to the utilization of coffee waste in the development of functional foods.